Estimating Permafrost Distribution in the Maritime Southern Alps, New Zealand, Based on Climatic Conditions at Rock Glacier Sites - Sattler, Katrin; Anderson, Brian; Mackintosh, Andrew; Norton, Kevin; de Róiste, Mairéad (Frontiers in Earth Science, 2016)
Alpine permafrost occurrence in maritime climates has received little attention, despite suggestions that permafrost may occur at lower elevations than in continental climates. To assess the spatial and altitudinal limits of permafrost in the maritime Southern Alps, we developed and tested a catchment-scale distributed permafrost estimate. We used logistic regression to identify the relationship between permafrost presence at 280 active and relict rock glacier sites and the independent variables a) mean annual air temperature and b) potential incoming solar radiation in snow free months. The statistical relationships were subsequently employed to calculate the spatially-distributed probability of permafrost occurrence, using a probability of ≥ 0.6 to delineate the potential permafrost extent. Our results suggest that topoclimatic conditions are favorable for permafrost occurrence in debris-mantled slopes above ~ 2000 m in the central Southern Alps and above ~ 2150 m in the more northern Kaikoura ranges. Considering the well-recognized latitudinal influence on global permafrost occurrences, these altitudinal limits are lower than the limits observed in other mountain regions. We argue that the Southern Alps’ lower distribution limits may exemplify an oceanic influence on global permafrost distribution. Reduced ice-loss due to moderate maritime summer temperature extremes may facilitate the existence of permafrost at lower altitudes than in continental regions at similar latitude. Empirical permafrost distribution models derived in continental climates may consequently be of limited applicability in maritime settings.